1998
DOI: 10.1111/j.1469-7793.1998.861bg.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in EPSC quantal size and quantal content at a central glutamatergic synapse in rat

Abstract: Developmental changes in amplitude and time course of single‐fibre‐evoked and spontaneous EPSCs mediated by AMPA and NMDA receptors at the endbulb‐bushy cell synapse of rats from 4 to 22 days of age were recorded using whole‐cell patch‐clamp methods in in vitro slices of cochlear nucleus. The mean conductance of the AMPA component of evoked EPSCs increased by 66 %, while that of the NMDA component decreased by 61 %, for 12‐ to 18‐day‐old rats cf. 4‐ to 11‐day‐old rats. The mean AMPA spontaneous EPSC conductanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
83
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 37 publications
14
83
4
Order By: Relevance
“…Our results are partially consistent with previous reports studying developmental plasticity of the calyx-type synapse in rat (Bellingham et al 1998;Chuhma & Ohmori, 1998;Taschenberger & von Gersdorff, 2000;Iwasaki & Takahashi, 2001).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our results are partially consistent with previous reports studying developmental plasticity of the calyx-type synapse in rat (Bellingham et al 1998;Chuhma & Ohmori, 1998;Taschenberger & von Gersdorff, 2000;Iwasaki & Takahashi, 2001).…”
Section: Discussionsupporting
confidence: 83%
“…Similar to what we have described, it has been reported that AMPAR-EPSCs show an age-dependent increase in amplitude at both the rat calyx of Held (Chuhma & Ohmori, 1998) and the endbulb of the Held synapse (Bellingham et al 1998). The former study attributed this increase to an upregulation of presynaptic voltage-gated Ca 2+ channels and release probability, whereas the latter suggested a postsynaptic increase in synaptic conductance.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…From 2 to 3 weeks of age, a decrease in average EPSP halfwidth from 0.78 to 0.55 ms is temporally correlated with a nearly fourfold increase in I K(LVA) . One possible mechanism underlying this change in EPSP duration is an acceleration in AMPA receptor kinetics, which has been described in studies of other auditory brainstem synapses (Bellingham et al, 1998;Lawrence and Trussell, 2000;Taschenberger and von Gersdorff, 2000;Joshi et al, 2004;MacLeod and Carr, 2005). However, this issue has not yet been addressed in the MSO.…”
Section: Properties and Developmental Regulation Of I K(lva) In Mso Pmentioning
confidence: 90%
“…In rat MNTB, AMPA receptor-mediated EPSCs as well as quantal synaptic currents acquire progressively faster kinetics, whereas NMDAR-mediated EPSCs diminish with age, as indicated by a 50% reduction in mean amplitude and faster decay kinetics from P5 to P14 (Taschenberger and von Gersdorff, 2000). The mean conductance of both spontaneous and evoked NMDA-EPSCs in the endbulb-bushy cell synapse decreased by more than half between P4-11 and P12-22 (Isaacson and Walmsley, 1995;Bellingham et al, 1998). Thus in both MNTB and cochlear nucleus, AMPA-receptor-mediated evoked synaptic responses become larger and faster, and NMDAR-mediated EPSCs diminish with age.…”
Section: Glutamate Receptors In Mammalian and Avian Auditory Developmentmentioning
confidence: 99%